Analisis Framing Pemberitaan Kebijakan Pemerintah Terkait Ketenagakerjaan sebagai Dampak Covid 19 di Kompas.com dan Malaysiakini - Palupi, Merry Fridha Tri; Irawan, Rahmat Edi (Universitas 17 Agustus 1945 Surabaya, 2020)
Abstract In the beginning of 2020 the mass media coverage was adorned with information about covid-19 outbreaks. The spread of covid-19 has crossed continents and even the rest of the world, making this period called as pandemic because it has infected 4.9 million people. The magnitude of this incident made the media including Kompas.com and Malaysiakini.com continue to convey information not only about health issues, but also other impacts in various fields such as law, politics, security and other social issues such as the economy and employment. This online news portal from Indonesia and Malaysia always reports on the development of covid-19 outbreaks in their respective countries. So much news was uploaded by the two online media that researcher only chose one news related to labor policy as the impact of covid-19 outbreaks. Using the theory of reality construction from Peter L. Berger, researcher analyzed the news framing using Robert N Enmant's model. The results showed an imbalance between the two online news portals because it only represented one party, where Kompas.com fetched news about wages from the point of view of the business world while Malaysiakini framed the appeal for the suspension of Eid Al-fitr leave that delivered by Mufti P Pinang as an opinion leader who respected by the Malaysian society. Keywords: Framing Analysis, Policy, Labor, Pandemic, Online Media.